Dampak Kegiatan Ekstrakurikuler Olahraga terhadap Nilai Karakter Siswa - Muhammad Zulfikar (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2023)
Sport extracurricular are only considered as an activity to optimize talent and interest in sports without realizing that sport extracurricular activities can also develop student’s character. This study aims to see the impact of sport extracurricular activities on the student’s character. This research used causal-comparative method. The population in this study were students of SMAN 11 Makassar who joined in sport extracurricular. Sampling in this study using purposive sampling technique as many as 30 students and control samples from students who are not incorporated in sport extracurricular activities as many as 30 people. Data is collected by using scale. The data analysis technique used is independent sample t test. Data analysis shows that there is a significant difference between the score of the character of both groups of research with the value of t arithmetic 4,848 bigger than t table (df (n-l) = 29 and a = 0,05) equal to 1,699. Scores of the students’s character who participated in sports extracurricular were greater than those who did not follow sport extracurricular. Score is in the good category with the number 80.27% so it can be concluded that the sport extracurricular activities have a positive impact on the student’s character.